Cascade utilization of energy in high temperature syngas to reduce energy consumption in biomass gasification processes - Sen Yao; Yajun Zhang; Jiaxi Xia; Tao Xie; Zhibin Zhang; Hai Li; Jianjun Hu (Case Studies in Thermal Engineering, 2023)
In this study, a biomass gasification process model based on the Gibbs free energy minimization principle is established to determine the optimal parameters of biomass gasification. Without affecting the product composition, the impact of the use of high-temperature syngas to heat the biomass and gasification agent on the thermal load of the system was discussed, aiming to reduce the overall energy consumption of the system by optimizing the energy flow.The results show that when the gasification temperature is 750 °C, the mass flow ratio of gasification agent to biomass is 1/1, and the pressure is 1 atm, the product quality is the best. Under the above conditions, using high-temperature synthesis gas to heat the gasification agent (steam) is more conducive to reducing energy consumption than using high-temperature synthesis gas to heat biomass. When two regenerators are set to heat biomass and gasification agent at the same time, it is found that the effect of heating gasification agent after heating biomass is better than heating gasification agent first, and the system heat load is reduced by up to 32.47 %, that is, about 1.83 kW.